Modified risk-stratified sequential treatment (subcutaneous rituximab with or without chemotherapy) in B-cell Post-transplant lymphoproliferative disorder (PTLD) after Solid organ transplantation (SOT): the prospective multicentre phase II PTLD-2 trial - Zimmermann, Heiner; Koenecke, Christian; Dreyling, Martin H.; Pott, Christiane; Duehrsen, Ulrich; Hahn, Dennis; Meidenbauer, Norbert; Hauser, Ingeborg A.; Rummel, Mathias J.; Wolf, Dominik; Heuser, Michael; Schmidt, Christian; et al. (Leukemia, 2022)
The prospective multicentre Phase II PTLD-2 trial (NCT02042391) tested modified risk-stratification in adult SOT recipients with CD20-positive PTLD based on principles established in the PTLD-1 trials: sequential treatment and risk-stratification. After rituximab monotherapy induction, patients in complete remission as well as those in partial remission with IPI < 3 at diagnosis (low-risk) continued with rituximab monotherapy and thus chemotherapy free. Most others (high-risk) received R-CHOP-21. Thoracic SOT recipients who progressed (very-high-risk) received alternating R-CHOP-21 and modified R-DHAOx. The primary endpoint was event-free survival (EFS) in the low-risk group. The PTLD-1 trials provided historical controls. Rituximab was applied subcutaneously. Of 60 patients enrolled, 21 were low-risk, 28 high-risk and 9 very-high-risk. Overall response was 45/48 (94%, 95% CI 83-98). 2-year Kaplan-Meier estimates of time to progression and overall survival were 78% (95% CI 65-90) and 68% (95% CI 55-80) - similar to the PTLD-1 trials. Treatment-related mortality was 4/59 (7%, 95% CI 2-17). In the low-risk group, 2-year EFS was 66% (95% CI 45-86) versus 52% in the historical comparator that received CHOP (p = 0.432). 2-year OS in the low-risk group was 100%. Results with R-CHOP-21 in high-risk patients confirmed previous results. Immunochemotherapy intensification in very-high-risk patients was disappointing.
CRIS-Team WoS Importer:2022-08-26